Synthesis of a New Granulated Polyampholyte and its Sorption Properties - Bekchanov Davron; Mukhamediev Mukhtar; Kutlimuratov Nurbek; Xushvaqtov Suyun; Juraev Murod (International Journal of Technology, 2020)
In this paper, characteristics of the interaction of an anion-exchange resin PPE-1 formed using phosphonic acid and granular polyvinyl chloride were investigated. In addition, a reaction order of 1.43 and an activation energy of 47.8 kJ/mol for phosphorylation were determined. The as-obtained polyampholyte was characterized by scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analysis, and Fourier transform infrared (FTIR) spectroscopy. Optimum conditions for obtaining a new polyampholyte that selectively adsorbs non-ferrous metal ions on the basis of granulated polyvinyl chloride were determined.  Sorption isotherms for non-ferrous metal ions were constructed, which were reasonably explained by Langmuir isotherms. Various thermodynamic parameters, such as isobaric-isothermal potential (?G), enthalpy (?H), and entropy (?S), were calculated to understand the nature of sorption. The examined polyampholyte selectively absorbed copper(II) ions.